The Historical Development of Employee Retention Theories - Chakib, Souad (The Pinnacle, 2024)
Workforce retention is vital in healthcare. Developing effective retention plans is important to reducing voluntary turnover. The first step to creating successful retention programs is understanding the basic theories concerning job satisfaction and organizational commitment. This paper aims to provide a literature review on the subject and examine the historical development of employee retention theories. The findings of this review suggested that considering the basic needs of employees increases commitment. Also, eliminating dissatisfiers (e.g., achievement, development, and reward) and enhancing satisfiers (e.g., working environment, pay, and security) motivates workers to achieve workplace goals. Additionally, employees work harder when they are rewarded and fairly treated relative to others. The review concluded that the models and theories surrounding employee retention can help provide insights into building an environment where employees show higher satisfaction levels and commitment to the organization.